ANALYSING NATIONAL DEVELOPMENT PLANS IN TURKEY REGARDING TEACHER TRAINING AND EMPLOYMENT - Serkan Ünsal; Reyhan Ağçam; Fahrettin Korkmaz (Informascope, 2018)
This research is motivated to investigate five-year national development plans (NPDs) prepared in Turkey between 1963 and 2013 with regard to teacher training and employment. The data were elicited from the plans in concern, and qualitatively analysed through content analysis. The preliminary findings demonstrated that the related decisions were made with a focus on three purposes: (i) to meet teacher shortage, (ii) to reduce the number of students per teacher, and (iii) to balance distribution of teachers nationwide. The reasons why most of them could not be successfully implemented might be listed as political instability, decisions taken without sufficient preparation, and inadequacy of efforts to implement NDPs. Even though certain decisions were taken considering teacher qualifications and competencies into account, quantitative concerns caused procrastination in their implementation. The study concludes with some practical implications for decision makers on the preparation and implementation of NDPs with respect to teacher training and employment.